(untitled) (Conference Zone, 2021)
This article discusses the visual presentation of the science being studied to students using the Venn diagram. In all sections of the science of theoretical mechanics it is shown that by applying this method it is possible to achieve the desired result in teaching students the basic words and phrases, concepts, theorems of science on a demonstrative basis.